Front Cover: Recent Advances in Rare Earth Doped Inorganic Crystalline Materials for Quantum Information Processing (Z. Anorg. Allg. Chem. 2/2018). Issue 2 (18th January 2018) - Kunkel, Nathalie; Goldner, Philippe
Abstract : The cover picture shows a two‐pulse‐photon‐echo sequence illustrated in form of Bloch spheres, a measurement which yields the optical transition coherence time or, equivalently, the homogeneous linewidth in material doped with trivalent rare earth ions. In the background, samples meant for quantum information processing are shown under UV‐light: the round dark‐red‐emitting samples are Y2 O3 :Eu 3+ transparent ceramics, whereas the orange‐red emitting cubes are Y2 SiO5 :Eu 3+, Er 3+ single crystals. Details are discussed in the article by Nathalie Kunkel and Philippe Goldner on page66 ff .